2015
DOI: 10.1111/bjd.14033
|View full text |Cite
|
Sign up to set email alerts
|

Vulvovaginal photodynamic therapy vs. topical corticosteroids in genital erosive lichen planus: a randomized controlled trial

Abstract: Vulvovaginal HAL-PDT seems to be an effective and safe treatment for GELP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…Treatment There is only one randomized controlled trial evidence to guide treatment of vulval erosive lichen planus. 68,69 Topical Treatment…”
Section: Managementmentioning
confidence: 99%
“…Treatment There is only one randomized controlled trial evidence to guide treatment of vulval erosive lichen planus. 68,69 Topical Treatment…”
Section: Managementmentioning
confidence: 99%
“…Prednisolone 5 mg pessaries have also been shown to be effective; however, some patients find these methods uncomfortable. Recent studies have reported positive outcomes with alternative formulations such as hydrocortisone acetate 10% foam …”
Section: Topical Therapiesmentioning
confidence: 99%
“…Algorithmic approach to treating VVLP. (Step 1) High‐potency steroids (i.e., clobetasol propionate 0.05% ointment) applied twice daily and then tapered once disease is controlled. Topical calcineurin inhibitor (i.e., tacrolimus 0.1% ointment) is another option that can be used in a similar regimen.…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a recently described treatment for patients with VLP and was found to have an equivalent efficacy to clobetasol ointment in a randomized controlled trial of 40 patients (Helgesen et al, 2015). Finally, patients with labial adhesions may benefit from surgery (Guerrero and Venkatesan, 2015).…”
Section: Lichen Planusmentioning
confidence: 99%